Exercise as a poisoned elixir: inactivity, inequality and intervention. Issue 4 (8th August 2018) - Williams, Oli; Gibson, Kass
Abstract: In this article, we theorise and explain Exercise is Medicine (EiM), as indicative of broader physical activity (PA) health promotion, from a sociological perspective through the lens of health equity. Data were collected through two independent ethnographic studies that bookend the EiM endeavour: the production of knowledge in the laboratory, and the creation and implementation of health policy and PA interventions. First, we demonstrate how conceptualising exercise as medicine assumes narrow pathology and (prescribed) solution a priori, which has given rise to a new form of movement intellectuals. Within such context, we explain how the study of physical (in)activity (especially by exercise scientists) is shaped by broader social and political contexts of the university sector and disciplinary legitimacy produced through alignment with other (medical) institutions. Second, we review the 'causes of the causes' of ill-health and wider social determinants of health as related to exercise. Presenting exercise as a 'therapy of freedom' that is to some extent epiphenomenal we examine the social inequalities and lifestyle drift which inhibit equitable access to this health promoting behaviour. We then outline an original qualitative methodological development: duoethnographic creative non-fiction, which has enabled the synthesis of two independent ethnographic studies. Findings of this accessible and engaging methodology, in the form of two stories, show the need for an alternative approach that values activity, prioritises equity and underscores methodological collaboration. For this reason, we conclude by proposing greater interdisciplinarity by aligning EiM with the Behavioural Justice Movement.